English Lexical Acquisition of Adult Learners in Instructional Settings: Issue on Lexical Input - Ahmad Azman Mokhtar; Rafizah Mohd Rawian; Paramjit Kaur a/p Karpal Singh (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2016)
This study examined the receptive and productive English vocabulary knowledge of tertiary students. Vocabulary Levels Test (VLT) consisted of three tests, namely Passive Vocabulary Test (PVT), Controlled Active Vocabulary Test (CAVT), and Free Active Vocabulary Test (FAVT) was used to collect the data. A total of 360 first-, second- and third-year university students were involved in the study. The findings revealed that majority of them had very limited lexical knowledge to use English as their second or foreign language, though formal exposures to English language had been given to them for at least 11 years before entering the tertiary level. In trying to unfold the unsuccessful attempt to enhance the students’ lexical competent through the present Malaysian education system, the issue of lexical input in terms of quantity and quality had been raised.